2009
DOI: 10.1111/j.1365-2753.2008.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival of intensive care and hospital patient cohorts compared with the general Australian population: a relative survival approach

Abstract: Adverse long-term survival of intensive care and hospital patients was demonstrated. For hospital patients there was additional infection-related mortality risk, not evident for ICU patients after case mix control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 56 publications
(127 reference statements)
2
25
0
Order By: Relevance
“…Our results are consistent with previous studies that have shown excess late mortality after sepsis relative to the general population27 28 and that the late mortality is not explained by differences in health status before sepsis 1029 30 These past studies, however, have been inconclusive because of the substantial risk of residual confounding by incomplete capture of patients’ baseline health status.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with previous studies that have shown excess late mortality after sepsis relative to the general population27 28 and that the late mortality is not explained by differences in health status before sepsis 1029 30 These past studies, however, have been inconclusive because of the substantial risk of residual confounding by incomplete capture of patients’ baseline health status.…”
Section: Discussionsupporting
confidence: 92%
“…Generally, the study populations included more males than females and the mean age of the cohorts ranged from 57 years to 63 years. Most of the studies measured severity of illness by using the APACHE II score 74,95,102,103,[107][108][109] and the mean score varied between 20.9 and 24.8 across the studies. Only limited information was reported on the proportion of patients with multiple organ dysfunction.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…The flow chart of studies included in the review is reported in Figure 38. Ten individual publications 74,93,95,102,103,[105][106][107][108][109] were identified from nine separate studies (with two publications coming from the same study).…”
Section: Studies Included In the Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term survival of patients following discharge from ICU has been shown to be lower than that of the general population. 115 For years 2 to 9 post randomisation, we therefore used the relative survival rates from an observational study of long-term survival following ICU discharge in an Australian population. 115 This study presented relative survival data for four subsets: hospitalised patients with either sepsis or not and ICU patients with sepsis or no evidence of sepsis; each of these was presented separately by sex.…”
Section: Analysis and Reportingmentioning
confidence: 99%